2022
DOI: 10.3390/v14122698
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Domestic Pigs with African Swine Fever Virus Isolated in 2019 in Mongolia

Abstract: African swine fever (ASF) is an infectious viral disease caused by African swine fever virus (ASFV), that causes high mortality in domestic swine and wild boar (Sus scrofa). Currently, outbreaks are mitigated through strict quarantine measures and the culling of affected herds, resulting in massive economic losses to the global pork industry. In 2019, an ASFV outbreak was reported in Mongolia, describing a rapidly progressing clinical disease and gross lesions consistent with the acute form of ASF; the virus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The present study also conducted an in-depth analysis of B646L (p72 Overall the results of the present study and a previous study (10)(11)(12) showed high stability and no genetic diversity in the B646L (p72) gene in the ASFV genome. One study conducted B646L (p72) gene in China also shows that ASFV genotype II is predominant among the 24 genotypes (13).…”
Section: Discussionsupporting
confidence: 73%
“…The present study also conducted an in-depth analysis of B646L (p72 Overall the results of the present study and a previous study (10)(11)(12) showed high stability and no genetic diversity in the B646L (p72) gene in the ASFV genome. One study conducted B646L (p72) gene in China also shows that ASFV genotype II is predominant among the 24 genotypes (13).…”
Section: Discussionsupporting
confidence: 73%
“…According to the criteria for the clinical course and pathogenicity of ASFV [ 2 ], the clinical signs, survival period, mortality rate, and pathological lesions observed in animals challenged with the two Korean ASFV isolates corresponded to those of the acute form of illness. This clinical disease progression of both Korean strains is similar to that of the highly virulent p72 genotype II strains, including Georgia 2007/1, Armenia 07, Pig/Heilongjiang/2018, VNUA/HY/Vietnam, and ASFV Mongolia/2019 [ 25 , 26 , 27 , 28 , 29 ]. The results demonstrated that both Korean ASFV strains were highly virulent.…”
Section: Discussionmentioning
confidence: 60%
“…Briefly, ASFV DNA was extracted and purified from samples using the automated magnetic bead KingFisher Flex equipment (ThermoFisher, 5400610, MA, USA) that utilizes the Total DNA Extraction Kit (GeneReach, Taiwan) as previously described ( 20 ). Quantitative real-time PCR for the detection of the ASFV gene encoding the p72 antigen (primers: Integrated DNA Technology, IA, USA, and probe: ThermoFisher, MA, USA) was performed in duplicate wells using PerfeCTa ® FastMix ® II (Quanta Biosciences, MA, USA) and following reagent and cycle parameters as previously described on the Stratagene Mx3005p Real-Time PCR Detection System (Agilent, CA, USA) ( 20 , 40 ).…”
Section: Methodsmentioning
confidence: 99%